The clergy and social mobility: the phenomenon of «raznochintsy» as the subject of social studies - Feofanov Aleksandr (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the present article the concept of “raznochintsy” is to be analysed. The author concludes that the “raznochintsy” cannot be considered as a kind of speciﬁc social layer. This name is assigned to a variety of categories of the population, and only one thing combines these categories in common - the opposition to other groups, whether nobles, merchants and clergy, depending on the situation, time and place. “raznochintsy” represent the phenomenon of language and social consciousness. Understanding “raznochintsy” as educated simpletons («radical intellectuals of not-noble origin») comes from Herzen and was canonized in Soviet historiography by authority of Lenin. In this deﬁnition the emphasis was placed on the opposition to the government, no gentry origin, revolutionary democracy. In modern historiography “raznochintsy” considered as a social group, located at the junction of the main classes (nobility, clergy, townspeople and peasants). “Raznochintsy” were ﬁrst of all outsiders, marginals. The very ﬁrst legal mention of “raznochintsy” (1701) determined them by the method of exclusion, as those who were not under the authority of the church oﬃ ce. In the confessional statements “raznochintsy” could refer to nobles (!) and domestic peasants, farmers (not included in other categories of the rural population), craft students and merchants. “Raznochintsy” in educational system were determined by opposition to other groups of students. For secular (Moscow University), this group were the nobles. In the religious schools (Kyiv-Mohyla, Slavic-Greek-Latin Academy) it was usual to determine “raznochintsy“ by contrast to natives of the clergy, so in the same number of “raznochintsy” nobles may be included.